A case report of renal mucormycosis masquerading as lower ureteric mass - Paighan, Nitin Madanrao; Sharma, Umesh; Saini, Abhishek (Indian Journal of Case Reports, 2024)
Isolated renal mucormycosis is rare. Its occurrence in immunocompetent patients is low. We present the case of a 45-year-old male presenting with flank pain and intermittent fever. On further evaluation, he was found to have a lower ureteric mass. Partial cystectomy and radical nephroureterectomy with pelvic node dissection were done. Histopathology was suggestive of mucormycosis. To the best of our knowledge, this is the only case presenting as a lower ureteric mass requiring partial cystectomy. Diagnosis of mucormycosis is challenging and requires a high index of suspicion.